2010
DOI: 10.21859/isv.4.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Partial Characterization of Viral Agent of Lettuce Big Vein in Tehran Province

Abstract: Background and Aims: The causal agents of viral lettuce big vein disease are two viruse, Lettuce big vein associated virus (Varicosavirus) and Mirafiori lettuce virus (Ophiovirus). These viruses have coat proteins of similar size but have different morphologies and serologically unrelated.The purpose of this study was to distinguish and detect LBVaV and MiLV in lettuce fields in Tehran Province. Patients and Methods: A total 344 samples with mosaic and big vein, head stunt, leaf deformation and motteling sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, Navarro et al (2004) in Spain, Fletcher et al (2005) in Australia, Pavan et al (2008) in Brazil, and Alemzadeh and Izadpanah (2012) in Iran in their conducted studies, determined that samples containing both viruses MiLBVV and LBVaV have been reported to cause LBVD. In addition, Al-Saleh et al (2015) and Heidari et al (2010) reported that MiLBVV and LBVaV alone or their mixed infections caused LBVD.…”
Section: Discussionmentioning
confidence: 99%
“…However, Navarro et al (2004) in Spain, Fletcher et al (2005) in Australia, Pavan et al (2008) in Brazil, and Alemzadeh and Izadpanah (2012) in Iran in their conducted studies, determined that samples containing both viruses MiLBVV and LBVaV have been reported to cause LBVD. In addition, Al-Saleh et al (2015) and Heidari et al (2010) reported that MiLBVV and LBVaV alone or their mixed infections caused LBVD.…”
Section: Discussionmentioning
confidence: 99%